'Outcasts from the world': same-sex sexuality, authority, and belonging in post-emancipation Jamaica. (3rd July 2019) - Thomas, Adam
ABSTRACT: In 1839, Jamaican plantation attorney Alexander Grant sued missionaries John Stainsby and Samuel Oughton for slander; they had accused Grant of 'lewd and indecent practices' with enslaved and apprenticed men. Missionaries and abolitionist supporters on one side, and Grant and the plantocracy on the other, used the scandal to challenge their opponents' suitability to shape post-emancipation society. The trials show that sex – and same-sex sexuality – was central to the contest for social authority. Several freedmen testified that Grant had coerced them into sexual interactions. Grappling with archival silences, the essay considers how the admissions affected their sense of masculinity and communal belonging.